2011
DOI: 10.1071/an10090
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Coopworth ewe lambs exposed to low levels of ryegrass endophyte (Neotyphodium lolii) alkaloids and allowed access to a mycotoxin deactivator

Abstract: During February–April, Coopworth ewe lambs grazing a pasture dominated by naturalised perennial ryegrass (PRG) exhibited slight signs of ill-thrift and heat stress. PRG represented 85% of the herbage; 90% of the PRG population was infected with Neotyphodium endophyte. Concentrations of ergovaline and lolitrem B in perennial ryegrass were each within the range 0.5–1.0 mg/kg DM during this period. Two groups of 30 lambs rotated weekly between two paddocks that offered 6 t DM/ha of mature, low-quality pasture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Respiration rate was similar in the NilAlk Heat and Alk TN treatment, suggesting that alkaloid ingestion increased heat load similarly to 38 °C heat. Grazing studies have found increases in rectal temperature and respiration rate over summer and autumn [ 4 , 12 ]. However, the amount of PRG alkaloid consumed by individual sheep was not measured due to the grazing nature of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration rate was similar in the NilAlk Heat and Alk TN treatment, suggesting that alkaloid ingestion increased heat load similarly to 38 °C heat. Grazing studies have found increases in rectal temperature and respiration rate over summer and autumn [ 4 , 12 ]. However, the amount of PRG alkaloid consumed by individual sheep was not measured due to the grazing nature of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Body temperatures were observed to rise above 41 °C and respiration rates increased, causing heat stress in sheep [ 1 ]. Previous work undertaken under grazing conditions in Australia have shown heat stress (increased respiration rate) when grazing Coopworth ewes on Victorian perennial ryegrass and subterranean clover mix [ 12 ]. The cost of PRGT in Australia has been estimated to be $100 million per annum [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have accessed postmortem reports from government laboratories [12][13][14] or used in-field trials in which very few or no animals were allowed to reach the severity of clinical signs associated with non-recovery; therefore; postmortem sampling has been difficult to achieve. 9,[15][16][17] A specific diagnosis of PRGT has historically been considered to be one of exclusion. Histopathological findings are difficult to interpret in isolation, as the diagnostic value of the classical PRGT lesion, namely, proximal axonal bodies of Purkinjie cells in the cerebellum, 18 is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of resistancesusceptibility to the subclinical effects of endophyte is unknown. Feed additives (Reed et al, 2011a) and immunization (Prestidge, 1993) are possible ways to counteract toxicoses, although the costs and diffi culty in administering these treatments may limit their adoption by farmers.…”
Section: Solutions To the Ryegrass-endophyte Dilemma: Lessons From Do...mentioning
confidence: 99%